A Proposed Integrative Framework among Green Target Costing, Cleaner Production, and Smart Manufacturing to Achieve Cost Reduction and Sustainable Competitive Advantage in Industrial Companies: A Review Paper - Al Mansour, Mahmoud Taha Mahmoud; Hameed, Noor Majid; Makki, Zain Aldin Mohammed Hassan; Abdul-Jabbar, Ayat Raad (NIU Journal of Management Sciences, 2026)
The purpose of this research is to introduce an integrated model incorporating three strategies utilized in the field of management and production in organizations; green target costing, cleaner production, and smart manufacturing. The objective of the paper is to demonstrate the role of these technologies in reducing costs and improving sustainable competitive advantage in today's industrial business environment. Based on the literature analysis, there appears to be a gap in current research due to the fact that many previous research papers focus on one strategy only, at best two, which makes the present study necessary to be conducted from a three-dimensional perspective. The research approach used in this study was analytical review and conceptual integration based on the latest literature in order to establish the relationship between the three technologies and construct an appropriate model for them. Based on the findings of the study, it is clear that the integration of these three technologies results in a synergic effect, increasing capabilities of firms to reduce costs, enhance quality of processes and minimize their environmental impacts. Finally, smart manufacturing acts as a platform that enables successful integration and standardization. The study suggests the use of a comprehensive management strategy within the context of industrial sustainability that combines cost management, production, and digital transformation together along with the creation of comprehensive performance indicators that incorporate the environmental, digital, and cost aspects, and further, calls for conducting practical studies that test the model suggested. In this regard, the present study makes a contribution to current literature through its unique contribution in incorporating environmental, digital, and cost aspects into one single framework. Keywords: Green Target Costing, Cleaner Production, Smart Manufacturing, Cost Reduction, Sustainable Competitive Advantage, Digital-Environmental Integration.